Ruins of sub-shrines surrounding the main Harshnath Temple - Temples of India Project Team (Jio Institute, 2024)
Around a dozen of sub-shrines were built on Harsha Hill in the 10th and 11th centuries CE. These were dedicated to various Brahmanical deities, as indicated by the architectural fragments. Unlike a Panchayatan temple or a planned temple complex, the irregular placement and size-proportions of these sub-shrines suggest a random and unplanned construction process over an extended period of time.